Manajemen Teknik Menyusui dan Implikasinya terhadap Kejadian Puting Susu Lecet Pada Ibu Nifas Di PMB Arni Yunita Kota Batam Kota Batam Tahun 2024 - Arini , Dianti; Amru, Desi Ernita; Siska , Dedy (Economics and Digital Business Review, 2024)
Failure in the breastfeeding process often causes problems, a problem that often occurs in breastfeeding mothers is the mother's lack of knowledge about correct breastfeeding techniques, which results in sores on the nipples, where the baby does not suck on the nipple up to the areola of the breast. The incidence of sore nipples based on the 2022 Indonesian Demographic Health Survey was 79.3 people. This research aims to determine the relationship between breastfeeding techniques and the incidence of sore nipples in postpartum mothers at PMB Arni Yunita, Batam City in 2024. This type of research uses a quantitative research design with a cross sectional research design. The population and sample used in this research were 47 postpartum mothers taken using the accidental sampling technique. The results of statistical tests using the chi square test showed that the p-value (0.000) was no more than α (0.05), so H0 was rejected and Ha was accepted, which means that there is a relationship between breastfeeding technique and the incidence of sore nipples in PMB Arni Yunita, Batam City. 2024. It is hoped that the public will be able to increase their knowledge and insight, including postpartum mothers, regarding the relationship between breastfeeding techniques and the incidence of sore nipples in postpartum mothers.